Model Pendekatan Perjuangan Emansipasi R.A.Kartini dari Perspektif Perjuangan Kesetaraan Gender Dewasa Ini (Sebuah Kajian Kepustakaan) - Mahyuni, Ida Ayu Putu (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 18 No 1 (2018)DO - 10.24843/PJIIB.2018.v18.i01.p08, 2018)
Raden Ajeng (R.A.) Kartini has been known as an Indonesian women’s emancipation fighter. In addition, R.A.Kartini is also known as the pioneer of the Indonesian nationalist movement, hence the state has appointed him a national independence hero (Moedjanto, 1983: IV). R.A.Kartini emancipation struggle is not done in a physical struggle, but done through the struggle of his thoughts or ideas. This paper reveals the emancipation struggle approach model R.A. Kartini from the perspective of the struggle for gender equality today (a literary review). To understand this problem, gender analysis is used as an analytical tool to understand the social realities of gender-differentiated relations between men and women. The concept of emancipation is not much different from the concept of struggle of gender equality known today, these two concepts aims to fight for the rights of women with men to be equal and equal in accordance with the context of the ability of each individual. Gender itself is a concept that refers to men and women who are distinguished not biologically or naturally but are distinguished on the basis of social and cultural constructs. Thus, both men’s and women’s societies can create, socialize, reinforce gender-based differences, so long as gender differences do not create injustice between men and women no matter the need to be sued, but the issue is when gender differences are constructed social and cultural causes of gender injustice that harm both men, especially for women (Fakih, 1999: 12). In connection With this there are several issues that need to be studied, among others: 1. How to model the approach to emancipation struggle R.A.Kartini in advancing the education of women? 2. How is the approach model of R.A.Kartini emancipation struggle fostering equality in family and marriage? 3. How does the emancipation struggle approach model of R.A.Kartini foster equality in improving the welfare of the people? All these issues will be examined from the perspective of today’s gender equality struggle.